How Geopolitical Events Reshape Armenia's Export Competitiveness - Movsisyan, Shushan (ՀՊՏՀ «Տնտեսագետ» հրատ․)
Against the background of the Russia-West conﬂict, Armenia's foreign trade has experienced substantial structural shifts in both product composition and geographical distribution. The signiﬁcant rise in exports is mainly driven by the re-export of gold and high-technology products. Although re-export has low value-add- ed, it signiﬁcantly impacts the economy. The present paper evaluates the changes in Armenia's export competitiveness following the Russo-Ukrainian war. The analysis reveals a decline in the competitiveness of Armenia's main export products, including ores, beverages, and several agricultural products. An increase in competitiveness was observed only in the sectors of tobacco, iron and steel, and certain textile products. Ռուսաստան-Արևմուտք հակամարտության խորապատկերում Հայաստանի արտաքին առևտուրը ենթարկվել է նշանակալի կառուցվածքային փոփոխությունների՝ թե' ապրանքային, թե' աշխարհագրական տեսանկյունից։ Արտահանման շեշտակի աճը պայմանավորված է ոսկու և բարձր տեխնոլոգիական ապրանքների վերաարտահանմամբ։ Թեև վերաարտահանումն ունի ցածր ավելացված արժեք, սակայն զգալի ազդեցություն է ունենում տնտեսության վրա։ Հոդվածում գնահատվել են Հայաստանի արտահանման մրցունակության փոփոխությունները 2019 և 2023 թթ.։ Վերլուծությունը ցույց է տալիս, որ հանքաքարի, խմիչքների, գյուղատնտեսական մի շարք ապրանքների մրցունակությունը նվազել է։ Մրցունակության աճ է գրանցվել միայն ծխախոտի, սև մետաղների, տեքստիլ մի շարք ապրանքների գծով։ На фоне конфликта Россия-Запад внешняя торговля Армении претерпела значительные струк турные изменения как в составе продукции, так и в географическом распределении. Существенный рост экспорта в основном обусловлен реэкспортом золота и высокотехнологичной про дукции. Хотя реэкспорт имеет низкую добавленную стоимость, его влияние на экономику значительное. В статье оцениваются изменения конкурентоспособности экспорта Армении после российско- украинской войны. Анализ показывает снижение конкурентоспособности основных экспортных товаров Армении, включая руды, напитки и некоторые сельскохозяйственные продукты. Увеличение конкурентоспособности было зафиксировано только в секторах табака, черных металлов и некоторых текстильных изделий.
Keywords: Armenia and the World